19 Adverse cardiac remodelling under pressure overload. a magnetic resonance imaging study in mice. (1st April 1997) - Kwiecinski, Jacek; Lennen, Ross; Gray, Gillian; Dweck, Marc; Jansen, Maurits
Abstract : Pressure overload, a hallmark of valvular heart disease and hypertension, is the leading cause of heart failure. With the progressive nature of this condition a better understanding of the process underlying the transition to heart failure is vital. Recent studies suggest that interstitial myocardial fibrosis occurs early in this transition and has a profound effect on cardiac function. The recently developed T1-mapping Cardiovascular Magnetic Resonance Imaging (CMR) technique has the potential to quantify the extracellular volume fraction (ECV) and therefore evaluate the expansion of the extracellular matrix (primarily diffuse fibrosis) over time. We aimed to assess the feasibility of CMR (including functional and ECV imaging) to monitor cardiac remodelling using an animal model of pressure overload heart disease. Fifteen mice were subjected to a 6 week Angiotensin-II infusion (AngII). CMR (cine and T1 mapping) was performed before and following Angiotensin II infusion at 2, 4 and 6 weeks. ECV was calculated from the T1 relaxation times pre and post-contrast infusion). Mean blood pressure increased from 65±12 (baseline) to 84±14 mmHg (p<0.001) and ECV increased from 24.28%±3.35% (baseline) to 30.03%±5.34% after 2 weeks of AngII (p=0.011). ECV plateaued at 4 and 6 weeks and stayed significantly higher compared to baseline (p=0.001). Cine imaging revealed left ventricular (LV) hypertrophy during infusion which remained stable at 4 and 6 weeks. Interestingly, systolic function was maintained after 2 and 4 weeks of AngII but was impaired at six weeks (EF 56.3% compared to 64.4% at baseline and 59.8%; 60.7%, at 2 and 4 weeks (p=0.014). This drop in cardiac performance was accompanied by a trend towards LV dilatation at 6 weeks compared to baseline (LV end diastolic volume 68 µl vs 63 µl, p=0.056). Prolonged pressure overload results in ECV expansion, LV hypertrophy and subsequent systolic dysfunction. T1 mapping CMR shows promise in monitoring this transition.